Effect of Sugarcane Bagasse-Derived Graphene Oxide on Bean Seed Germination - Flávia Gomes da Silva; Elibe Silva Souza; José Daniel da Silva Fonseca; Sophia Dionizio Melo; Joanna Elzbieta Kulesza Barros; Bráulio Silva Barros (Materials Research)
As demand for sustainable agriculture grows, materials like graphene oxide (GO) are gaining attention due to their potential to boost crop productivity and reduce environmental impacts. This study reports the synthesis of GO from sugarcane bagasse using ferrocene as a catalyst. The material was characterized by Raman spectroscopy, FTIR, XRD, and SEM. To evaluate its effects on bean seeds, seed priming was done with GO concentrations of 0, 10, 50, and 100 mg/L, followed by ultrasound treatment and germination tests. Higher GO concentrations (100 mg/L) were phytotoxic, reducing germination rates and speed index (GSI). In contrast, lower concentrations (10 and 50 mg/L) increased moisture content in shoots and roots, positively influencing growth. The highest mean shoot length (13.3 cm) was observed at 50 mg/L, while root length did not differ significantly. These findings highlight GO's potential to improve water retention and growth at optimized concentrations, offering promise as a sustainable agricultural input.